2020
DOI: 10.1002/brb3.1941
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and aerobic fitness in relation to local and interhemispheric functional connectivity in adolescents’ brains

Abstract: Introduction Adolescents have experienced decreased aerobic fitness levels and insufficient physical activity levels over the past decades. While both physical activity and aerobic fitness are related to physical and mental health, little is known concerning how they manifest in the brain during this stage of development, characterized by significant physical and psychosocial changes. The aim of the study is to examine the associations between both physical activity and aerobic fitness with brains’ functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 96 publications
(112 reference statements)
0
5
0
Order By: Relevance
“…Physiologically, EF plays a pivotal role in cognitive functions [ 20 ], including: (i) inhibition (i.e., resisting habits, temptations, or distractions); (ii) updating (i.e., retaining and using information); and (iii) cognitive flexibility [ 21 , 22 ]. Various neuropsychological paradigms, such as the Flanker task, the 2-back task, and the more-odd shifting task, can be used to measure the performance of EF.…”
Section: Introductionmentioning
confidence: 99%
“…Physiologically, EF plays a pivotal role in cognitive functions [ 20 ], including: (i) inhibition (i.e., resisting habits, temptations, or distractions); (ii) updating (i.e., retaining and using information); and (iii) cognitive flexibility [ 21 , 22 ]. Various neuropsychological paradigms, such as the Flanker task, the 2-back task, and the more-odd shifting task, can be used to measure the performance of EF.…”
Section: Introductionmentioning
confidence: 99%
“…We expected that the ongoing activation of visual and auditory cortices would modulate engagement in a task-specific manner and would reflect the level of attention required by the cross-modal attention task. Based on previous findings (Hernández et al, 2021; Ruotsalainen et al, 2020, 2021) suggesting a stronger role of PA than AF for functional brain measures, we also hypothesized that PA level would specifically show an association with the efficiency of neural engagement of sensory cortices to task-relevant signals (hence, difference between attended vs. unattended condition). To test our hypotheses, the attended and unattended cortical SSRs in each sensory cortex were contrasted between groups with high vs. low PA/AF in typically developed adolescents.…”
Section: Introductionmentioning
confidence: 97%
“…To better understand the specific associations that either PA or AF levels have with brain structure and function, the same group of subjects needs to be used for both comparisons. Supporting the divergent role of PA vs. AF for the brain, earlier studies have indicated that AF is associated more strongly with brain structural measures than PA (Ruotsalainen et al, 2019(Ruotsalainen et al, , 2020, but PA might influence brain functional properties, which underlie cognition in adolescents (Hernández et al, 2021;Ruotsalainen et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…These adaptations contribute to increases in gray matter volume (GMV) particularly in regions relevant for cognitive functions like the hippocampus (Firth et al., 2018 ) and white matter volume (WMV), along with enhanced neural and receptor activity, leading to improvements in cognitive (De Sousa Fernandes et al., 2020 ) and motor functions (El‐Sayes et al., 2019 ). Moreover, higher levels of PA have been associated with greater structural and functional connectivity (FC) as observed through neuroimaging techniques (Ruotsalainen et al., 2021 ; Soldan et al., 2022 ; Stillman et al., 2018 ), in networks critical for maintaining multiple aspects of overall brain health and hindering cognitive decline (Stillman et al., 2018 ). Despite these findings, the precise mechanisms underpinning exercise‐induced neuroplasticity remain incompletely understood (El‐Sayes et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%